Incidence of malignancies in patients with multiple sclerosis versus a healthy matched cohort: A population-based cohort study in the Netherlands using the PHARMO Database Network. (September 2022) - Kuiper, Josephina G.; Overbeek, Jetty A.; Foch, Caroline; Boutmy, Emmanuelle; Sabidó, Meritxell
Highlights: Patients with MS may have risk factors for malignancies. An analysis has not been undertaken in the Netherlands thus far. An increased incidence of total malignancies cannot be excluded. However, could be due to a different distribution of risk factors. Abstract: This study estimated the incidence of malignancy in patients with multiple sclerosis (MS) versus a matched general population cohort in the Netherlands. Adults with a diagnosis of MS between 2006 and 2014 in the General Practitioner (GP) Database of the PHARMO Database Network with ≥ 1 year of patient history were matched to four non-MS individuals based on year of birth, sex, and GP practice. Patients were followed-up until the earliest malignancy diagnosis, death, or end of data collection. Age-adjusted incidence rates (IR) were measured overall and by cancer type. Standardized incidence ratios (SIR) were calculated as the ratio of stratification-specific IRs in the MS and non-MS cohorts. A total of 1, 692 MS patients were matched to 6, 768 non-MS patients. Age-adjusted IR of any malignancy, excluding non-melanoma skin cancer (n = 27), in the MS cohort was 48.3 (95%CI:30.1–66.5) per 10, 000 PY. An increased incidence of any malignancy was observed in the MS cohort versus the non-MS cohort (SIR 1.8 [95%CI:1.1–2.5]). The most commonly observed malignancies in the MS cohort were breast cancer (n = 8; IR 20.4 [95%CI:6.3–34.5] per 10, 000 PY) and melanoma (n = 6; IR 14.8 [95%CI:3.0–26.7] per 10, 000 PY). The corresponding SIR observed between cohorts was 1.4 (95%CI:0.4–2.4) and 3.4 (95%CI:0.7–6.2), respectively. While the small increased incidence of malignancy in the MS cohort could be an artefact created by a different distribution of risk factors, an increased incidence of malignancy in MS patients in the Netherlands cannot be excluded.